Penggunaan komunikasi non-verbal bahasa tubuh dalam desain instruksional pelatih dan atlet kategori tanding pencak silat - Darmawansah, Andika; Putro, Raden Hartopo Eko (Jurnal Komunikasi Profesional, 2019)
Instruction is a form of information exchange with the aim to provide understanding and influence on the behavior of martial arts athletes by the trainers. Clear instructions, will facilitate the athlete in understanding the message delivered, will automatically also affect the performance of athletes in the game. Therefore, to facilitate and clarify in the delivery of instructions, the need for non-verbal body language as a supporter of such verbal instructions. Body language is a process of exchanging information that is done by using limbs as a medium of information. Although every body movement has a variety of meanings for everyone. However, in martial arts the units of Unitomo Surabaya made certain movements which were considered to be able to support verbal instruction, then the movement was givenÂ  a meaning which was in accordance with the rules of usage and on the basis of mutual agreement by trainers and athletes, and the communication process was made as tradition by the group.Keywords: instructional design; non-verbal communication; athlete